Impact of the Early Islamic Conquests on the Social Structure of Madina - Mohamed Omer, Elkhalifa (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Impact of the Early Islamic Conquests on the Social Structure of Madina